THE PROBLEM OF ASSESSING THE VALUE OF BUSINESS IN MODERN CONDITIONS (World Economics and Finance Bulletin, 2023)
The article deals with methodological problems related to business valuation. The authors proceed from the assumption that in modern business conditions in the evaluation process should be considered as a system that includes two bases: a company as a property complex and, at the same time, the material basis of business, and, in fact, the business itself, as a certain economic activity, conducted in certain technical, socio-economic conditions. At the same time, it is shown that when assessing business as an activity, it is necessary to take into account the industry prospects of this activity, changing in the process of technological development of economic systems.
Keywords: valuation; business; property